Optimisation of railway terminal design and operations using villon generic simulation model - Adamko, Norbert; Klima, Valent (Transport, 2008)
Railway service terminals (nodes) are the places of a railway network equipped with costly technology based on high complexity technological procedures demanding a high degree of coordination and control skills. Great effort is therefore exerted to find an optimal configuration of infrastructure to extensively exploit technical and human resources and to effectively organize technological procedures. Due to the complex system, a simulation model seems to be the only suitable tool for performing investigations under realistic conditions. The paper focuses on the possible utilization of simulation methods to support the design and optimisation of infrastructure process control algorithms in railway terminals. The paper also deals with the most important properties and possibilities offered by the simulation tool Villon and comments on the experience gained during its utilisation. The tool supports tactical (middle‐term) and strategic (long‐term) planning usually related to infrastructural or operational proposals which are supposed to guarantee the optimal (or at least effective) behaviour of the modelled terminal.First published online: 27 Oct 2010